Experimental Study on the Riverbed Coarsening Process and Changes in the Flow Structure and Resistance in the Gravel Riverbed Downstream of Dams - Zhou, Yinjun; Lu, Jinyou; Jin, Zhongwu; Li, Yuan; Gao, Yu; Liu, Yujiao; Chen, Peng (Frontiers in Environmental Science, 2021)
Following the construction of a reservoir, sediment is intercepted, which greatly reduces the sediment concentration in the discharged flow. This reduction causes riverbed scouring and flow structure adjustments downstream, thereby impacting the river habitat. This study used the generalized flume test with different bed sand compositions and discharge rates to simulate the scouring adjustment process of a sand pebble riverbed channel downstream of a reservoir. The results show that the bed sediment composition affects the water surface gradient, scour depth, turbulence intensity, and sand resistance directly after final scouring. Coarse-grained bed sediment demonstrated the greatest final turbulence intensity and sand resistance, while bed sediments with reduced coarseness exhibited a greater scouring degree; the resistance for sand grains of moderate coarseness showed the greatest change. Sand resistance was exponentially and positively correlated with the median grain size and the fractal dimension of bed sediment mass. The mass fractal dimension expression was suitable for the analysis of bed sand grain-size distribution; it contributed to the calculation of grain resistance with fewer hydraulic parameters. The relationship between the mass fractal dimension and the adjusted grain resistance was also established, which can aid the calculation of the resistance changes in sandy gravel-bed river reaches downstream of reservoirs, enabling the prediction of their effects on aquatic habitats.